Síntese de nanopartículas semicondutoras de seleneto de zinco (ZnSe) aquoso e análise dos subprodutos decorrentes dessa síntese - Pinto, Alexandre Henrique (Universidade Federal de São Carlos, 2012)
Zinc selenide (ZnSe) is a semiconductor material, which band gap is about 2.7 eV. It has many applications as blue light emission diode, data storage devices, laser diodes and waveguides optical fibers. Despite these several applications, ZnSe, generally, is synthesized in organic solvents, such as: trioctylphosphine oxide (TOPO), hexadecylamine (HDA) or octadecene (ODE). These synthetic methods are carried out at high temperatures, about 250oC. Moreover, being synthesized in organic media makes these nanoparticles unable to be dispersed in aqueous systems, and consequently, they are unable to be applied in biological media, unless some post preparative procedure is applied. In view those shortcomings, in this work, ZnSe was synthesized in aqueous media, having ZnCl2 as zinc source, NaHSe, as selenium source, which was synthesized from reduction of elemental selenium by sodium borohydride (NaBH4), and L-cisteine as capping agent. Initially, a 22 factorial design was applied. Temperature and pH were the factors studied in this factorial design, aiming to determine the influence of these factors on crystallographic coherence dominium calculated through Scherrer equation. Despite synthesis in aqueous media applies lower temperatures (90 oC), it has some disadvantages, for instance, the generation of some byproducts. Among these byproducts are: trigonal or amorphous elemental selenium and L-cistine, however, sometimes, these compounds can not be tracked through x-ray diffraction (XRD), since they are either amorphous or are below the detection limit of this technique. In this sense, Raman spectroscopy plays an important role in this work, since it is able to track these byproducts in a range of some months. Finally, a simple decantation process was carried out in order to separate these byproducts in different aliquots.
Synthesis of zinc selenide (znse) semiconductor nanoparticles in aqueous media and analysis of the byproducts yielded from this synthesis
Keywords: Físico-química; Seleneto de zinco; Selênio amorfo; Selênio trigonal; Raman, Espectroscopia de; Semicondutores; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA